Weblink sources for cybermetric analysis - Orduña-malea, Enrique (Anuario ThinkEPI, 2012)
In the 2012 edition of the Ranking web of world universities there has been a major change in methodology, forced by changes in the source for obtaining external links to university websites. Following the closure of Yahoo site explorer, the new tool currently in use is MajesticSEO. The main services and products that offer data links and their suitability for use in cybermetric analysis are discussed. We conclude that there is a need for tools created specifically for cybermetric analysis, given the evolution of search engines and the limitations of other products aimed mainly at search engine optimization rather than at informetric analysis.